Combined calcium pretreatment and ultrasonic/microwave drying to dehydrate black chokeberry: Novel mass transfer modeling and metabolic pathways of polyphenols. (January 2023) - Zhu, Rui; Shen, Juan; Law, Chung Lim; Ma, Xiaoxuan; Li, Dandan; Han, Yongbin; Kiani, Hossein; Manickam, Sivakumar; Tao, Yang
Abstract: In this study, black chokeberries were dehydrated by sequential calcium pretreatment and ultrasonic/microwave drying. The investigation focused on exploring the mechanisms of water transport and metabolic pathways of polyphenols. A diffusional model was modified by considering the factors such as shrinkage, porosity and temperature-dependent water diffusivity to simulate the moisture transport. Accordingly, the Spatio-temporal evolutions of cytoplasm water, extracellular water and total water content in black chokeberry throughout drying were successfully revealed. On the other hand, the quality attributes involved in the metabolic pathways of polyphenols, i.e., free/bound phenolics, cell wall pectin, polyphenol oxidase (PPO) or peroxidase (POD), and viscoelastic properties under these drying treatments were intensively analysed. Through correlation analysis, it was found that CaCl2 pretreatment strengthened the oxidation of free procyanidin B2 by PPO. In contrast, both ultrasound and microwave drying weakened the negative influence of PPO on the stability of free rutin. Besides, temperature rise promoted the loss of free polyphenols and the degradation of cell wall pectin, weakening the attachment of bounded-caffeic acid on the cell wall. This investigation provides new physical and chemical understandings about fruit drying and reveals the potential benefits of hybrid drying technologies. Highlights: CaCl2 immersion was combined with ultrasound/microwave drying to dry black chokeberry. A mass transfer model with temperature rising, shrinkage and porosity was built. Decline of free procyanidin B2 was caused by both enzymatic and thermal degradations. Ultrasound and microwave treatments alleviated enzymatic degradation of free rutin. Transformation of cell wall ASP to WSP contributed to the loss of bound caffeic acid.